Bitcoin High-Frequency Microstructure Dynamics and Returns Predictability - Chepelau, Andrej (2024)
This thesis explores topic of Bitcoin’s high-frequency microstructure and predictability of its price. While this topic has been studied extensively in traditional finance and capital markets such as stocks, commodities and currencies, the same can’t be said about cryptocurrencies, as it is a relatively new asset. This leads to a need to be able to determine differences between microstructure and price process between traditional and new markets. This work achieves that by reproducing parts of work by Ait-Sahalia et al. (2022), which concerns itself with stock data, and then examining the differences in results and price predictability while providing some guidance on lower bound of what can be predicted when it comes to Bitcoin’s high-frequency microstructure. The aim of the study is to inspect and describe dissimilari- ties between aspects of stock and Bitcoin microstructure and also to describe the interactions of Bitcoin microstructure variables and it’s price.